2015
DOI: 10.1166/jnn.2015.9658
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Thermoelectric Properties of Co-Doped ZnO Synthesized by Sol–Gel

Abstract: Zinc oxide (ZnO) has attracted increasing attention as one of the most promising n-type thermo-electric materials, but its practice use was limited by high thermal conductivity and low electrical conductivity. Therefore, we herein prepared Co-doped ZnO nanoparticles by sol-gel method and then compressed nanoparticles into bulk materials through spark plasma sintering. The thermo-electric properties, including electrical conductivity, Seebeck coefficient, thermal conductivity, and ZT value, have been investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 0 publications
4
7
0
Order By: Relevance
“…It can be seen that the power factor PF = dS 2 ( Figure 10A), and finally, the thermoelectric conversion efficiency (ZT) ( Figure 10B), has been improved compared to previous similar work. 17…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen that the power factor PF = dS 2 ( Figure 10A), and finally, the thermoelectric conversion efficiency (ZT) ( Figure 10B), has been improved compared to previous similar work. 17…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
“…Thermoelectric properties can be recovered by reducing thermal conductivity (κ), and increasing electrical conductivity (σ), and Seebeck coefficient ( S ). Experimental and theoretical studies suggest that substitution ZnO with transitional metal elements (M‐ZnO) such as Mn, Ce, Co, Ni, and Al can improve optical, electrical, and thermoelectric properties . Cobalt has received much recognition as a candidate material because the ionic radius of Co 2+ is close to that of Zn 2+ (a Co 2+ = 0.058 nm, a Zn 2+ = 0.06 nm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the sintered T-NZnOP (especially, T-NZnOP-750C and T-ZnOP-950C) obtained results that exhibited an increase in PF which improved the total ZT values as compared to the previous nanostructured undoped ZnO samples. 6,7,49,50 Henceforth, the dimensionless gure of merit (ZT) is as shown in Fig. 6c.…”
Section: -19)mentioning
confidence: 99%
“…As doping increases, grain size increases and it reduces the charge carrier scattering at grain boundaries, and hence, there is an increase in mobility as well as conductivity [59]. Wu et al [60] prepared cobalt-doped ZnO (0%-10%) by the sol-gel method and showed that the substitution of Co ++ for Zn ++ could improve the electrical conductivity due to the increase in carrier concentration. In addition, we estimated several activation energies using equation (5), indicative of various conduction mechanisms involved in the doped samples.…”
mentioning
confidence: 99%